Needs Assessment Survey for the Management of Kidney Cancer. Issue 3 (May 2017) - Lavallée, Luke T.; Fitzpatrick, Ryan; Cnossen, Sonya; Witiuk, Kelsey; Wood, Lori; Basiuk, Joan; Vanhuyse, Marie; Tanguay, Simon; Pautler, Stephen E.; Finelli, Antonio; Jewett, Michael A.; Cagiannos, Ilias; et al.
Abstract : Introduction: : In this study we determined self‐perceived knowledge gaps and continuing medical education preferences among Canadian urologists and medical oncologists related to the treatment of patients with kidney cancer. Methods: : A needs assessment survey was created by the Quality Initiative group of the Kidney Cancer Research Network of Canada using an iterative feedback process. The survey determined knowledge gaps and continuing medical education preferences pertaining to 23 previously validated quality indicators of kidney cancer care. Topics included screening, diagnosis, prognosis, surgical management, systemic therapies and followup care. The survey was distributed via e‐mail to Canadian urologists and medical oncologists. Results: : Among the 164 respondents 121 (74%) were urologists and 43 (26%) were medical oncologists. The majority of respondents practice in academic (72, 57%) or large urban community centers (40, 32%). Of the 23 quality indicators examined 14 were designated as priority continuing medical education topics based on perceived inadequate knowledge or high interest in the topic. Priority topics were similar for urologists and medical oncologists, and covered the spectrum of kidney cancer care with an emphasis on hereditary kidney cancer and management of advanced disease. Most respondents preferred that continuing medical education be delivered through in person, case based group discussions. Conclusions: : Canadian urologists and medical oncologists report similar knowledge gaps and continuing medical education preferences regarding kidney cancer care. Priority topics include screening for hereditary kidney cancer and management of advanced disease.